2023
DOI: 10.1038/s41564-023-01495-8
|View full text |Cite|
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi heterokaryons have two nuclear populations with distinct roles in host–plant interactions

Jana Sperschneider,
Gokalp Yildirir,
Yanina S. Rizzi
et al.

Abstract: Arbuscular mycorrhizal fungi (AMF) are prominent root symbionts with a multinucleate cytoplasm that can carry thousands of nuclei deriving from two parental strains and varying in relative abundance in a large syncytium. Here, we set out to improve our understanding of such remarkable genetics by resolving the nuclear genomes of all publicly available AMF heterokaryons using PacBio HiFi and Hi-C sequencing. We find that all AMF heterokaryons carry two sets of homologous chromosomes, where genes associated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 87 publications
0
27
0
Order By: Relevance
“…The combination of Hi‐C and HiFi PacBio sequencing identified two sets of homologous chromosomes among thousands of coexisting nuclei in AMF heterokaryons. These two sets of related genomes differ in content, gene expression, and epigenetic regulation, and the abundance of each set varies depending on the host plant and environmental conditions (Sperschneider et al ., 2023).…”
Section: Harnessing Genomics To Enhance Our Understanding Of the Deve...mentioning
confidence: 99%
“…The combination of Hi‐C and HiFi PacBio sequencing identified two sets of homologous chromosomes among thousands of coexisting nuclei in AMF heterokaryons. These two sets of related genomes differ in content, gene expression, and epigenetic regulation, and the abundance of each set varies depending on the host plant and environmental conditions (Sperschneider et al ., 2023).…”
Section: Harnessing Genomics To Enhance Our Understanding Of the Deve...mentioning
confidence: 99%
“…Chromosome‐level genome sequencing coupled to Hi‐C analyses of R. irregularis strains showed that nuclei are organized in a euchromatic compartment, containing many genes with core functions, and a heterochromatic and heavily methylated compartment, rich in repetitive sequences but also in genes for predicted secreted proteins highly expressed in planta (Yildirir et al ., 2022; Sperschneider et al ., 2023). This suggests that during the symbiotic phase the chromatin condensation in AM fungi could be, to some extent, under the control of the host plant.…”
Section: Insights On Small Rna and Rnai In Am Fungimentioning
confidence: 99%
“…Using RepeatModeler and RepeatMasker, recent analyses of R. irregularis chromosomelevel datasets indicated that strains of this species carry an average of 50% of TE 9,12 .…”
Section: A Curated Database Reveals New Te Families In Rhizophagus Ir...mentioning
confidence: 99%
“…However, only one third of their repeat content could be classified, and thus on average 30% of all available genomes are composed by unclassified TE sequences 9,12,19,21 . To address this, we used five chromosome-assembly level from homokaryon and four heterokaryon strains to generate curated repeat libraries.…”
Section: A Curated Database Reveals New Te Families In Rhizophagus Ir...mentioning
confidence: 99%
See 1 more Smart Citation